WOMANIST PERSPECTIVE ON INTERSECTIONALITY IN WALKER’S ‘THE COLOR PURPLE’ - Dr. Nailah Riaz; Bisma Khalid (International Journal of Contemporary Issues in Social Sciences, 2024)
The main focus of this study is on Black feminism and how this specific type of feminism addresses intersectionality . Intersectionality plays a major role in shaping the experiences of different women. The focus of this research is on different elements of intersectionality highlighted in The Color Purple, which attempts to recognize the status of women in the patriarchal society of their time. This study consists of three problems to be analyzed. The first is, “ How does womanist perspective offer understanding of intersectionality in The Color Purple? The Second is, “What are the womanist principles reflected in the novel through female characters? “ and the third is, “ How can a womanist lens be applied to male characters in the novel to understand intersectionality?”. This research is qualitative and the data collected for this research is also qualitative. The primary source of data for this research is the novel ‘ The Color Purple’ and the secondary sources of data are also used to conduct this research, which includes academic journals and theories on Womanism. By analysing this literary work, this study helped to understand how women of the black community face challenges due to their race and gender’s intersection. It highlights the importance of intersectional feminism discourse.